Evaluation Of the Use Of the Merdeka Teaching Platform Application by Teachers at SD 057/1 KM V Muara Tembesi - Harmita, Harmita; Tersta, Friscilla Wulan; Pratama, Linardo; Aprillitzavivayarti, Aprillitzavivayarti (Jurnal Prajaiswara, 2025)
Introduction/Main Objectives: The Merdeka Mengajar (PMM) Platform was developed to support the Merdeka Curriculum by offering flexibility for teachers in designing technology-based learning. It features independent training, diagnostic assessments, and digital resources aimed at improving learning effectiveness. Background Problems: : Despite its benefits, PMM implementation faces challenges such as limited technology access, low teacher proficiency in using the platform, and minimal supporting training. This study evaluates PMM’s effectiveness using the CIPP (Context, Input, Process, Product) model. Novelty: This study offers a comprehensive evaluation of PMM using the CIPP model. Research on PMM’s effectiveness in primary education remains limited, making this study a new contribution to understanding teacher use. Research Methods: A qualitative case study was conducted at SD Negeri 057/1 KM V Muara Tembesi. Data were collected through interviews with the principal and teachers, observations of PMM usage, and analysis of relevant documents. Finding/Results: PMM assists teachers in preparing materials, conducting assessments, and accessing digital resources. However, limited internet and training remain key barriers. Conclusion: PMM has the potential to enhance learning, but its success depends on infrastructure support and ongoing teacher training. The study provides recommendations for improving PMM implementation.